Constitutional Values And Judges Morals In The Decision of The Constitutional Court Number 90/PUU-XXI/2023: Review of The Flow of Natural Law - Nainggolan, Indra Lorenly; Nina Zainab (KRTHA BHAYANGKARA, 2024)
The decision of the Honorary Council of the Constitutional Court stated that the Constitutional Court judges who examined case Number 90/PUU-XXI/2023 were proven to have violated the right to refuse. The right to refuse is part of the independent and impartial principle of the Constitutional Court. There has been a conflict of interest between the norms being tested and the Constitutional Court judges. Conflicts of interest are constitutional and moral violations. What are the juridical consequences of Constitutional Court Decision Number 90/PUU-XXI/2023 which violates the constitution and morals from the perspective of natural law philosophy? This research uses a normative juridical research method with a conceptual approach, a statutory approachs and a case approach. The results of the discussion have found that in the MKMK decision that the judge consciously and deliberately ignored constitutional principles regarding the right to refuse in Law Number 48 of 2009 concerning Judicial Power. Overruling the right to refuse is tantamount to overruling constitutional principles. Judges place constitutional values in practice as semantic values. Apart from that, there was a moral violation which was assessed by the lack of awareness not to review case Number 90/PUU-XXI/2023 due to a conflict of interest. Awareness comes from conscience and is closely related to integrity, independence and impartiality. The integrity of judges as enforcers and guardians of the constitution is at stake. Moral and legal principles in the constitution are two things that go hand in hand in natural law philosophy.